Peer Assessment Practices in Indonesian Higher Education: The Students’ Views - Alfi Hidayatu Miqawati (Politeknik Negeri Jember, 2019)
The shift of paradigm in English Language Teaching (ELT) has brought teachers and practitioners to seek ways to assess their students resembling to instructional activities in the classroom. Students are not only perceived as objects of assessment but they are given a role as subjects who have big role and involvement in the assessment process. As a result, their perspectives are particularly essential because the power of assessment directly impacts on their motivation and attitudes towards schooling. This study attempted to investigate students’ perception on the implementation of peer assessment in their process of learning English and the impacts of the assessments toward their language learning motivation and achievement. Its design was descriptive qualitative and involved 9 students of non English Department. The data was collected through intensive and in-depth interview. The result showed that the students have different dimentions of views toward peer assessment and they thought that the means of assessment implemented helps them gain their motivation and know better on what to achieve during their process of learning.